2002
DOI: 10.2113/gscanmin.40.2.693
|View full text |Cite
|
Sign up to set email alerts
|

A Solution to the Crystal Structures of Bismutite and Beyerite

Abstract: The crystal structures of bismutite, Bi 2 (CO 3 )O 2 , a 3.865(2), b 3.862(2), c 13.675(6) Å, V 204.1(2) Å 3 , space group Imm2, Z = 2, and beyerite, CaBi 2 (CO 3 ) 2 O 2 , a 3.7729(5), b 3.7742(7), c 21.726(4) Å, V 309.4(1) Å 3 , space group Immm, Z = 2, have been refined to R indices of 0.0206 and 0.0145 on the basis of 184 and 258 unique reflections. Although the cell and the distribution of diffraction intensities obey tetragonal symmetry, for both these minerals, attempts to solve the structure with tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 6 publications
1
46
0
2
Order By: Relevance
“…However, the line placed at *32°in the XRD pattern vanished. We deduce that a residual amount of additional compound, resulting probably from not fully reacted substrates, most likely bismuth carbonate (BiO) 2 CO 3 , that were removed after the sample was thermally treated [15,36,37]. Moreover, the disorder increased slightly, since the FWHM of the (112) line from Pbam symmetry and (400) line from I23 symmetry, e.g., placed at 35.77(2)°changed by 0.08.…”
Section: Xrd Determination Of the Crystal Structurementioning
confidence: 96%
“…However, the line placed at *32°in the XRD pattern vanished. We deduce that a residual amount of additional compound, resulting probably from not fully reacted substrates, most likely bismuth carbonate (BiO) 2 CO 3 , that were removed after the sample was thermally treated [15,36,37]. Moreover, the disorder increased slightly, since the FWHM of the (112) line from Pbam symmetry and (400) line from I23 symmetry, e.g., placed at 35.77(2)°changed by 0.08.…”
Section: Xrd Determination Of the Crystal Structurementioning
confidence: 96%
“…Bismuth-containing materials, such as BiOX (X = Cl, Br, I) [16,17], BiVO 4 [18], Bi 2 WO 6 [19], and (BiO) 2 CO 3 [20], exhibit not only good visible light photocatalytic activity but also high chemical stability. Among these materials, the bismuth subcarbonate (BiO) 2 CO 3 which belongs to Aurivillius-related oxide family with a typical ''sillén'' phase structure [20] is particularly efficient for the degradation of organic dyes [21][22][23][24][25] and isopropyl alcohol [22].…”
Section: Introductionmentioning
confidence: 99%
“…Bi 2 O 2 CO 3 is a typical "Sillén" phase, in which Bi-O layers and (CO 3 ) layers are inter-grown with the plane of the (CO 3 ) group orthogonal to the plane of the Bi-O layer. 21,22 The internal layered structure of Bi 2 O 2 CO 3 would guide the lower growth rate along certain axis compared with that for other axes, to form 2D morphologies such as sheet-like or plate-like products. 8,23,24 Previous work has demonstrated that Bi 2 O 2 CO 3 hierarchical structures assembled by nanosheets exhibit high activity towards the photodegradation of RhB as well as the mixed solution of MB and MO, due to their exposed (001) facets.…”
Section: -17mentioning
confidence: 99%